Complex left Caputo fractional inequalities - ANASTASSIOU, George A. (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
Here we present several complex left Caputo type fractional inequalities of well known kinds, such as of Ostrowski, Poincare, Sobolev, Opial and Hilbert- Pachpatte. Mathematics Subject Classification (2010): 26D10, 26D15, 30A10.